Zoomed cosmological simulations of Milky Way sized halos in f(R)-gravity - Arnold, Christian; Springel, Volker; Puchwein, Ewald (Arxiv, 2016)
We investigate the impact of f(R) modified gravity on the internal properties of Milky Way sized dark matter halos in a set of cosmological zoom simulations of seven halos from the Aquarius suite, carried out with our code MG-GADGET in the Hu & Sawicki f(R) model. Also, we calculate the fifth forces in ideal NFW-halos as well as in our cosmological simulations and compare them against analytic model predictions for the fifth force inside spherical objects. We find that these theoretical predictions match the forces in the ideal halos very well, whereas their applicability is somewhat limited for realistic cosmological halos. Our simulations show that f(R) gravity significantly affects the dark matter density profile of Milky Way sized objects as well as their circular velocities. In unscreened regions, the velocity dispersions are increased by up to 40% with respect to LCDM for viable f(R) models. This difference is larger than reported in previous works. The Solar circle is fully screened in
Gesehen am 30.10.2017